The Principal's Strategy in Implementing the Tahfidzul Qur'an Program - Miftahul Jannah; Yusrizal Yusrizal; Khairuddin Khairuddin (AL-ISHLAH: Jurnal Pendidikan, 2023)
Strategy in education is the basic framework for an action to be taken. This strategy acts as a controller in carrying out his duties and responsibilities as school principal. The objective of this study was to ascertain the principal's strategic approach, evaluate the outcomes of the tahfizh programme, and identify the elements that either facilitated or hindered the program's implementation. The employed methodology is a qualitative approach, utilising data collection approaches such as observation, interviews, and documentation analysis. The research subjects were the principal, tahfizh coordinator, tahfizh teachers and students. The data analysis technique used is descriptive qualitative analysis with data reduction techniques, data presentation, and drawing conclusions. The results of the study show that: The principal's strategy in implementing the tahfizh program is by arranging programs that involve tahfizh learning schedules, tahfizh learning materials, determining the qualifications of tahfizh teachers to be recruited, determining memorization targets and determining the methods needed to run the program. The results of the implementation of the tahfizh program are increasing student interest in becoming a hafizh, increasing student enthusiasm for learning both in the field of tahfizh lessons and other lessons, increasing noble character which is reflected in social interactions between students, teachers and parents. The implementation of the tahfizh program also won several awards in the Qur'an tahfizh competition. The supporting factor for the tahfizh program is that the program is well structured, both in scheduling, providing facilities and infrastructure and choosing methods. The inhibiting factor is that it occurs when there are students who have not been able to read the Qur'an properly. It can slow down the process of memorizing other students because of the time needed by students who have not been able to have more.